2011
DOI: 10.1051/0004-6361/201117377
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of the Enceladus water torus withHerschel

Abstract: Cryovolcanic activity near the south pole of Saturn's moon Enceladus produces plumes of H 2 O-dominated gases and ice particles, which escape and populate a torus-shaped cloud. Using submillimeter spectroscopy with Herschel, we report the direct detection of the Enceladus water vapor torus in four rotational lines of water at 557, 987, 1113, and 1670 GHz, and probe its physical conditions and structure. We determine line-of-sight H 2 O column densities of ∼4 × 10 13 cm −2 near the equatorial plane, with a ∼50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 37 publications
9
91
0
Order By: Relevance
“…If, however, such disc-averaged observations were undertaken at any other time in Saturn's seasonal cycle, the ring contribution would be non-negligible. The ring contribution was added to the measurement error as a source of uncertainty in the spectral modelling, and we will further discuss the importance of the Enceladus water torus (Hartogh et al 2011) in Sect. 4.2.…”
Section: Estimating Saturn's Ring Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…If, however, such disc-averaged observations were undertaken at any other time in Saturn's seasonal cycle, the ring contribution would be non-negligible. The ring contribution was added to the measurement error as a source of uncertainty in the spectral modelling, and we will further discuss the importance of the Enceladus water torus (Hartogh et al 2011) in Sect. 4.2.…”
Section: Estimating Saturn's Ring Contributionmentioning
confidence: 99%
“…Sub-saturated tropospheric H 2 O was detected by de in the 5-μm region. However, an external influx of oxygen compounds from micrometeoroid ablation, cometary impacts or a connection to Saturn's rings and satellites (particularly Enceladus, Hartogh et al 2011) has long been postulated as a potential source. Water was previously detected in Saturn's stratosphere in the sub-millimetre by ISO Moses et al 2000b) and SWAS (Bergin et al 2000), but recent observations by Herschel/HIFI (Hartogh et al 2011) have revealed that an extended cold water vapour torus exists around Saturn's equatorial plane due to plume activity on Enceladus.…”
Section: Water H 2 Omentioning
confidence: 99%
“…Both comets were the subjects of deep investigations using Herschel, including measurements of the D/H ratio in water (Hartogh et al 2011;Bockelée-Morvan et al 2012). The observations of 103P/Hartley 2 presented here were executed in the framework of the guaranteed time key programme "Water and related chemistry in the Solar System" (Hartogh et al 2009). Those of C/2009 P1 (Garradd) correspond to an open time proposal.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its significant brightness (m v ∼ 8.5 at perihelion), it was an interesting target for the study of distant cometary activity. We report here on observations undertaken at r h = 3.3 AU post-perihelion with the PACS (Poglitsch et al 2010) andSPIRE (Griffin et al 2010) instruments on Herschel (Pilbratt et al 2010), in the framework of the Herschel guaranteed time key project called "Water and related chemistry in the Solar System" (Hartogh et al 2009). These observations are complemented by production rate measurements of several species with the Nançay radio telescope and the 30-m telescope of the Institut de Radioastronomie millimétrique (IRAM) at 3.2-3.3 AU pre-and post-perihelion.…”
Section: Introductionmentioning
confidence: 99%